TRANSPORT OF Cr3+, Cd2+, Pb2+, AND Ag+ IONS THROUGH BULK LIQUID MEMBRANE CONTAINING p-tert-BUTYLCALIX[4]ARENE –TETRACARBOXYLIC ACID AS ION CARRIER - Maming Maming; Jumina Jumina; Dwi Siswanta; Hardjono Sastrohamidjojo (Indonesian Journal of Chemistry, 2007)
The research on transport of Cr3+, Cd2+, Pb2+, and Ag+ through bulk liquid membrane using p-tert-butylcalix[4]arene-tetracarboxylic acid as ions carrier has been conducted. The aims of this research were to determine optimum condition, efficiency, and selectivity of transport of the ions carriers to those ions. Both optimum condition and efficiency of transport were obtained by determination of transported ions concentration with pH variation of source phase, ionic carrier concentration, nature of stripping agent in target phase, and transport time. The transport selectivity of ions carrier was obtained from experiments of equimolar mixture ions transport competition. Amount of Cr3+, Pb2+, Cd2+, and Ag+  transported across liquid membrane were about 6, 80, 84  and 87 % respectively after being transported for 48 h. The ion carrier  was selective for both Pb2+ ion  (separation factors are 9.6 for Ag+ ion, 1.9 for  Cd2+ ion and infinite for Cr3+ ion) and Ag+ ion (separation factors are 1.8 for Cd2+ and infinite for both Pb2+ and Cr3+ ions). This system represents a proton-coupled transport with flow of protons in the opposite direction.